FACTORS INFLUENCING VACCINE EFFICACY - A GENERAL REVIEW - A. Rashid; K Rasheed; M. Akhtar (Journal of Animal and Plant Sciences, 2009)
Vaccines are essential tools for disease prevention and the control of disease spread. Their universal acceptance is based on the recognition of their high effectiveness and good safety record. Vaccines have significantly contributed to a steady decline in the mortality and morbidity that is caused by infectious diseases. Sometimes, vaccine failure to protect from disease is usually due to problems with either client education or compliance with good animal management practices. A number of factors involve in the vaccine efficacy. Some are beyond the control of either veterinarian or farmer. The present article aims to study the factors influencing the vaccine efficacy.
Keywords: Vaccines; Effectiveness; Veterinarian; Farmer